2020
DOI: 10.1111/codi.15375
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual dysfunction in patients with perianal Crohn's disease

Abstract: Aim Over the past 10 years, several studies have focused on sexuality in patients with Crohn's disease. Very few of them specifically focused on perianal disease (PD). This study aimed to compare the prevalence of sexual dysfunction (SD) in Crohn's disease patients with active PD versus controls without active PD. Method Patients from 14 French centres with active PD, defined by the presence of symptomatic ulceration, fistula or stenosis, were arbitrarily included. They were compared with controls from the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…This literature review highlights the multifaceted sexual di culties women who live with IBD have, such as painful intercourse, vaginismus, lower sexual satisfaction and desire and di culty with orgasm [13,[18][19][20][21][22][23]. The literature also highlights that there is a bidirectional relationship between depression and sexual dysfunction [16,17] which has been described in the broader literature by Velten and Milani [37].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This literature review highlights the multifaceted sexual di culties women who live with IBD have, such as painful intercourse, vaginismus, lower sexual satisfaction and desire and di culty with orgasm [13,[18][19][20][21][22][23]. The literature also highlights that there is a bidirectional relationship between depression and sexual dysfunction [16,17] which has been described in the broader literature by Velten and Milani [37].…”
Section: Discussionmentioning
confidence: 94%
“…Boudiaf et al [19] explored sexual dysfunction speci cally for those who had a diagnosis of perianal CD and found that of the 64 French women who participated in their study, 66% had sexual dysfunction. Rivière et al [22] reported that of the 192 French women with IBD in their study 53.6% had sexual dysfunction scores and similarly, a Spanish study found that almost half of their participants had sexual dysfunction [21].…”
Section: Ibd and Sexual Functioningmentioning
confidence: 99%
“…During the literature review, we also identified that psychiatric disorders could be a contributing factor in understanding the relationship between perianal fistula disease and erectile dysfunction. Depression has been shown to be the most frequently reported predictive factor for sexual function impairment in perianal diseases ( Boudiaf et al, 2021 ). Moreover, mood disorders, including depression, are more common in benign anorectal diseases and are considered significant risk factors for sexual function impairment ( Akkoca et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…pCD is associated with poor quality of life and a high level of disability. Poor work productivity, sleep disturbance, and sexual dysfunction are frequently reported by these patients, leading to substantial morbidity ( Vollebregt et al., 2018 ; Vester-Andersen et al., 2015 ; Boudiaf et al., 2021 ). Furthermore, pCD is associated with more aggressive CD phenotypes and a greater likelihood of anal canal carcinoma, intestinal resection, and definitive stoma (see Fig.…”
Section: Introductionmentioning
confidence: 99%